2021
DOI: 10.1590/2317-1545v43232700
|View full text |Cite
|
Sign up to set email alerts
|

Use of quantitative colorimetry and visual evaluation for color characterization of triticale seeds after phenol reaction

Abstract: Quantitative colorimetry can be used to characterize the color of triticale seeds submitted to the phenol test. This study aimed to characterize the color of triticale seeds after the phenol test by visual color evaluation and quantitative colorimetry using the CIELAB color space. The evaluated seeds came from 88 triticale genotypes from the IDR-Paraná Germplasm Bank. The colorimetric data for L (lightness) and chromaticity coordinates a* and b* of the seeds before and after phenol reaction were obtained using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Among the traits obtained by GroundEye ® , hue, CIELab-b, and circumference were those that most contributed to explaining genetic divergence between the families. Other authors described similar results using the GroundEye ® system to assess diversity based on the CIELab color system to differentiate seeds of different species (Krause et al 2017, Fachi et al 2019, Gentallan Junior et al 2019, Torres et al 2019, Buratto et al 2021. Fachi et al (2019) evaluated 98 FSFs of P. edulis and reported that the use of color and geometry descriptors, obtained by GroundEye ® , contributed to quantifying genetic divergence between families.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Among the traits obtained by GroundEye ® , hue, CIELab-b, and circumference were those that most contributed to explaining genetic divergence between the families. Other authors described similar results using the GroundEye ® system to assess diversity based on the CIELab color system to differentiate seeds of different species (Krause et al 2017, Fachi et al 2019, Gentallan Junior et al 2019, Torres et al 2019, Buratto et al 2021. Fachi et al (2019) evaluated 98 FSFs of P. edulis and reported that the use of color and geometry descriptors, obtained by GroundEye ® , contributed to quantifying genetic divergence between families.…”
Section: Discussionmentioning
confidence: 85%
“…The use of the GroundEye ® system proved to be efficient in differentiating the FSFs of passion fruit based on geometric and color variables, as reported for other species. Buratto et al (2021) concluded that the CIELab color system is efficient and practical for classifying the color of triticale (Triticosecale wittmack) seeds subjected to the phenol test. The same was observed by Gentallan Junior et al (2019), who reported that the CIELab color system was efficient to distinguish different shades of brown in Pili (Canarium ovatum Engl.)…”
Section: Discussionmentioning
confidence: 99%
“…This is especially a case when large diversity panels are characterized for seed traits and get grouped in a few classes based on such subjective assessment. Buratto et al (2021) proposed that qquantitative colourimetry can be used to characterize the colour of seeds. They compared visual colour evaluation and quantitative colourimetry of triticale seeds using the CIELAB colour space.…”
Section: Seed Colour Classes In Beansmentioning
confidence: 99%